2021
DOI: 10.1186/s12887-021-02507-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical characteristics of severe pertussis in infants and children: a retrospective study

Abstract: Background The incidence of pertussis shows an increasing trend in recent years, but some clinicians often lack sufficient understanding of the clinical characteristics and risk factors for severe pertussis, and more effective measures should be taken to reduce the incidence and mortality of pertussis in young infants Methods A retrospective study was conducted, and 184 infants and children with pertussis who had been hospitalized in the Department… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…The infants with pertussis were divided into two groups according to the severity of disease: severe pertussis group and non-severe pertussis group. The diagnosis of non-severe pertussis and severe pertussis was consistent with the report of Wang et al [ 14 ]. Those who met the clinical diagnostic criteria for pertussis in the "Suggestions for Diagnosis and Treatment of Pertussis in Children in China" and those who were detected positive by B. pertussisis culture or polymerase chain reaction (PCR) test were diagnosed as non-severe pertussis [ 15 ].…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…The infants with pertussis were divided into two groups according to the severity of disease: severe pertussis group and non-severe pertussis group. The diagnosis of non-severe pertussis and severe pertussis was consistent with the report of Wang et al [ 14 ]. Those who met the clinical diagnostic criteria for pertussis in the "Suggestions for Diagnosis and Treatment of Pertussis in Children in China" and those who were detected positive by B. pertussisis culture or polymerase chain reaction (PCR) test were diagnosed as non-severe pertussis [ 15 ].…”
Section: Methodssupporting
confidence: 90%
“…Pertussis caused by infection with B. pertussisis predominantly seen in infants, some occurrence of complications could lead to severe pertussis, such as pneumonia, apnea, leukocytosis, pulmonary hypertension, seizures and encephalopathy [ 14 , 16 , 17 ]. A recent 5-year surveillance study from Switzerland reported an incidence of laboratory confirmed pertussis of 38.8/100,000 in infants less than 12 months old [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WBC count on admission was associated with outcome and mortality in multiple studies. 15,[26][27][28] We demonstrated a similar result, higher WBC count was associated with severe disease. A high WBC count could sludge pulmonary arteries, or toxins produced by B. pertussis could lead to pulmonary hypertension, a major complication of pertussis in neonates and infants.…”
Section: Factors Associated With Severe Diseasesupporting
confidence: 66%
“…We suspect that most of the patients were colonized by community-acquired A. baumannii, given that samples were taken upon admission to hospitalization . The presence of A. baumannii in relation to whooping cough have also been reported previously, for example, it has been detected in children with whooping cough as a complication, causing severe pertussis and pneumonia [ 21 ]. However, this is the first report of this pathogen in young pediatric patients with community-acquired A. baumannii.…”
Section: Main Textmentioning
confidence: 56%